Do graphic health warning labels on cigarette packages deter purchases at point-of-sale? An experiment with adult smokers. Issue 3 (1st April 2019) - Shadel, William G; Martino, Steven C; Setodji, Claude M; Dunbar, Michael; Scharf, Deborah; Creswell, Kasey G
Abstract: This experiment tested whether the presence of graphic health warning labels on cigarette packages deterred adult smokers from purchasing cigarettes at retail point-of-sale (POS), and whether individual difference variables moderated this relationship. The study was conducted in the RAND StoreLab (RSL), a life-sized replica of a convenience store that was developed to evaluate how changing POS tobacco advertising influences tobacco use outcomes during simulated shopping experiences. Adult smokers ( n = 294; 65% female; 59% African-American; 35% White) were assigned randomly to shop in the RSL under one of two experimental conditions: graphic health warning labels present on cigarette packages versus absent on cigarette packages. Cigarette packages in both conditions were displayed on a tobacco power wall, which was located behind the RSL cashier counter. Results revealed that the presence of graphic health warning labels did not influence participants' purchase of cigarettes as a main effect. However, nicotine dependence acted as a significant moderator of experimental condition. Graphic health warning labels reduced the chances of cigarette purchases for smokers lower in nicotine dependence but had no effect on smokers higher in dependence.